Dimensions of Tarbiya in Seerat un Nabi : Inculcating Socio-Moral Values in Children from Childhood to Puberty - Qurashi, Inayat Ul Haq; kalyar advocate, Tahir Ashraf (University of Wah Journal of Social Sciences, 2023)
Moral and social development of an individual is one of the important aims of education. This paper presented the inculcation of social and moral values in children from early age to puberty. The study was basically done by focusing on the Prophetic methodology of Tarbiyah. For clear understanding, the author divided the children into two age groups: 1) early age to seven years 2) seven years to puberty. The author addressed some important questions related to the moral and social development including a) why moral and social development of children is important b) which socio-moral values should be inculcated in the children c) what is guidance in Seerat-ul-Nabi to inculcate these moral values d) which measures need to be taken for the moral and social transformation of children e) which factors cause problems in avoiding the moral and social development f) who are the stakeholders and responsible to nurture children morally and socially. The author tried to respond these questions by seeking guidance from the Tarbiyah methodology of Holy Prophet PBUH. In the light of cited literature and drawn conclusion, the author also recommended some suggestions to make research applied and practical. Qualitative cum experimental methodology was employed in this academic work. Key words: Islamic values, Tarbiyah, morality, social values, children